Reason and Rationality - Amoretti, Maria Cristina; Vassallo, Nicla (Philosophische Analyse / Philosophical Analysis ;, 2013)
Reason and rationality represent crucial elements of the self-image of human beings and have unquestionably been among the most debated issues in Western philosophy, dating from ancient Greece, through the Middle Ages, and to the present day. Many words and thoughts have already been spent trying to define the nature and standards of reason and rationality, what they could or ought to be, and under what conditions something can be said to be rational. This volume focuses instead on the relationships of reason and rationality to some relevant specific topics, i.e., science, knowledge, gender, politics, ethics, religion, aesthetics, language, logic, and metaphysics, trying to uncover and clarify both the connections and differences in their various characterisations and uses.